Wigner distribution function formalism for superconductors and collisionless dynamics of the superconducting order parameter - Amin, M.H.S.; Bezuglyi, E.V.; Kijko, A.S.; Omelyanchouk, A.N. (Фізико-технічний інститут низьких температур ім. Б.І. Вєркіна НАН України, 2004)
A technique for studying collisionless dynamics of a homogeneous superconducting system is
developed which is based on Riccati parametrization of the Wigner distribution function. The
quantum evolution of the superconducting order parameter, initially deviating from the equilibrium
value, is calculated using this technique. The effect of a time-dependent BCS paring
interaction on the dynamics of the order parameter is also studied.